1996
DOI: 10.2307/3870416
|View full text |Cite
|
Sign up to set email alerts
|

MFP1, a Novel Plant Filament-Like Protein with Affinity for Matrix Attachment Region DNA

Abstract: The interaction of chromatin with the nuclear matrix via matrix attachment regions (MARs) o n the DNA is considered to be of fundamental importance for higher order chromatin organization and regulation of gene expression. Here, we report a novel nuclear matrix-localized MAR DNA binding protein, designated MAR binding filament-like protein 1 (MFPl), from tomato. In contrast t o the few animal MAR DNA binding proteins thus far identified, MFPl contains a predicted N-terminal transmembrane domain and a long fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(83 citation statements)
references
References 30 publications
(42 reference statements)
3
79
1
Order By: Relevance
“…Previous results have shown that MFP1 is present in a nuclear matrix preparation derived from tobacco NT-1 suspension-cultured cells (Meier et al, 1996). However, we noticed that the fraction of total MFP1 detectable in the nuclear matrix varied from experiment to experiment (data not shown).…”
Section: A Variable Amount Of Mfp1 Is Tightly Associated With the Nuccontrasting
confidence: 51%
See 4 more Smart Citations
“…Previous results have shown that MFP1 is present in a nuclear matrix preparation derived from tobacco NT-1 suspension-cultured cells (Meier et al, 1996). However, we noticed that the fraction of total MFP1 detectable in the nuclear matrix varied from experiment to experiment (data not shown).…”
Section: A Variable Amount Of Mfp1 Is Tightly Associated With the Nuccontrasting
confidence: 51%
“…Whereas the majority of MFP1 is highly ␣ helical and predicted to form a coiled-coil structure (Meier et al, 1996), the first 150 amino acids lack a coiled-coil structure but contain two hydrophobic domains (indicated as red bars in Figures 3 and 5). The first hydrophobic domain is similar to transmembrane domains from a variety of membrane attached proteins (Meier et al, 1996), indicating that the N terminus of MFP1 might act as a membrane-attachment domain. To test whether the hydrophobic domains are involved in the targeting of MFP1 to the speckles, we constructed two N-terminal deletion mutants of MFP1-mGFP ( Figure 5A).…”
Section: The Hydrophobic N Terminus Of Mfp1 Is Required For Its Corrementioning
confidence: 99%
See 3 more Smart Citations